Parlaying digital imaging and communications in medicine and open architecture to our advantage: the new Department of Defense picture archiving and communications system...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Cawthon MA (Journal of Digital Imaging)
The Department of Defense (DoD) undertook a major systems specification, acquisition, and implementation project of multivendor picture archiving and communications system (PACS) and teleradiology systems during 1997 with deployment of the first systems in 1998. These systems differ from their DoD predecessor system in being multivendor in origin, specifying adherence to the developing Digital Imaging and Communications in Medicine (DICOM) 3.0 standard and all of its service classes, emphasizing open architecture, using personal computer (PC) and web-based image viewing access, having radiologic telepresence over large geographic areas as a primary focus of implementation, and requiring bidirectional interfacing with the DoD hospital information system (HIS). The benefits and advantages to the military health-care system accrue through the enabling of a seamless implementation of a virtual radiology operational environment throughout this vast healthcare organization providing efficient general and subspecialty radiologic interpretive and consultative services for our medical beneficiaries to any healthcare provider, anywhere and at any time of the night or day. Copyright (c) 1999 by W.B. Saunders Company